Pembuatan Biobriket Cangkang Sawit dan Tandan Kosong Kelapa Sawit Menggunakan Muffer Furnace - Mutiara Indah; Abu Hasan; Robert Junaidi (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The problem of energy crisis is one of the main problems faced by almost all countries in the world. This energy crisis occurs due to the dependence on the fulfilment of the world fuel energy from fossil fuels. The increasing use of fossil energy causes greenhouse gases, so the climate is unstable and the temperature of the earth and the sea level are rising. Therefore, efforts are needed to overcome the problem of energy crisis. One way to reduce it is the utilisation and use of palm oil processing waste (POPW) into bio-briquettes, where the components come from palm shells and empty bunches. The aim of this study is to evaluate the properties of biobriquettes in order to obtain optimal results in obtaining the quality of biobriquettes that are analysed to meet the quality of briquettes according to quality standards. Based on the analysis carried out, the highest analysis results were obtained on sample S5 with a ratio of 00:100 and 8% glue, including: proximate analysis (water content 5.4%, ash content 8%, volatile matter 13.5%), calorific value 5941.10 cal / gr and combustion rate 0.2305 gr / minute. The results obtained comply with the quality requirements for charcoal briquettes based on SNI No. 01-6235-2000.